Primary students’ ability to convert verbal expressions into mathematical models in fraction materials - Shanti Nurhidayah; Salsabila Anindiyah; Yudistira Indra Prahasta Putra Elwanda; Setiyani; Khodari, Rahmad; Gunawan (Universitas Jambi, Indonesia, 2025)
This research aimed to describe the patterns of errors and the forms of scaffolding needed by students to convert verbal expressions into mathematical models in fraction material. This research used a descriptive qualitative method. The research involved 4th-grade students from a selected elementary school in Cirebon City. Data were collected through tests and interviews. The instruments used were a written mathematical representation ability test and an interview question guide. The data analysis techniques employed included data reduction, data presentation, and conclusion drawing. The results showed that high-ability students effectively recognize numerators, denominators, and problem contexts, enabling accurate translation of verbal expressions into a mathematical model. Medium-ability students were able to answer most questions but still struggled to distinguish between numerators and denominators. On the other hand, low-ability students often had difficulty understanding verbal questions, which led to errors in writing fractions.